Identity of the local and macroscopic dynamic elastic responses in supercooled 1-propanol. Issue 31 (27th July 2021) - Weigl, Peter; Hecksher, Tina; Dyre, Jeppe C.; Walther, Thomas; Blochowicz, Thomas
Abstract : As a surprising, non-trivial result of comparing the local elastic properties with those from macroscopic shear measurements, it was found that the responses are identical, even in their time dependence. Abstract : Glass-forming liquids are well known to have significant dynamic heterogeneities, leading to spatially grossly varying elastic properties throughout the system. In this paper, we compare the local elastic response of supercooled 1-propanol monitored by triplet state solvation dynamics to the macroscopic dynamic shear modulus measured by a piezo-electric gauge. The time-dependent responses are found to be identical, which means that the dynamic macroscopic shear modulus provides a good measure of the average local elastic properties. Since the macroscopic shear modulus of a dynamically inhomogeneous system in general is not just the average of the local moduli, there was no reason to expect such a result. This surprising finding not only provides constraints for models of dynamical heterogeneities in glass-forming liquids, but also allows for a fairly straightforward check on elastic models for glassy dynamics.